Synthesis of Platinum Nanoparticles Using Pluronic® F108NF and Catalytic Effect - Ko*, W.B.; Hong, S.K.; Lee, J.H. (Asian Journal of Chemistry, 2011)
This study examined the efficient preparation of platinum nanoparticles using pluronic® F108NF and K2[PtCl4] in water under nonclassical condition. The nanoparticles were characterized by transmission electron microscopy and ultraviolet-visible spectroscopy. The platinum nanoparticles were used as a catalyst to reduce 4-nitrophenol to 4-aminophenol with NaBH4. The resulting product was confirmed by UV-vis spectroscopy and liquid chromatography-mass spectroscopy